Rates of evolution of avirulence phenotypes and DNA markers in a northwest European population of Puccinia striiformis f. sp. tritici - HOVMØLLER, MOGENS S; JUSTESEN, ANNEMARIE F (Molecular ecology, 2007)
The effects of evolutionary processes in fungal pathogen populations may occur more rapidly and display larger effects in agricultural systems than in wild ecosystems because of human involvement by plant breeding and crop management. In this study, we analysed the rate of evolution in three lineages of a northwest European population of a biotrophic and asexual reproduced fungal pathogen, Puccinia striiformis f. sp. tritici, causing yellow rust on wheat. Pathogen samples were collected between 1975 and 2002 in the UK and Denmark, and assayed for 14 individual avirulence/virulence alleles and up to 234 amplified fragment length polymorphism (AFLP) primer pairs producing approximately 17 000 AFLP fragments. The large number of fragments and a targeted sampling of isolates allowed a reconstruction of phylogenies in great detail, i.e. no homoplasy and a representation of sequential, evolutionary steps by pathogen samples. A recent, phenotypic loss of avirulence was observed at least once for loci corresponding to P. striiformis f. sp. tritici resistance Yr2, Yr3, Yr4, Yr7, Yr9, and Yr15, whereas Avr6 and Avr17 were lost independently in all three lineages, corresponding to 16 events of loss of avirulence (emergence of virulence). The opposite process, restoration of avirulence, was observed for Yr9 and Yr32. An interpretation of phenotypic changes within lineages as independent mutation events resulted in mutation frequencies from 1.4 x 10⁻⁶ to 4.1 x 10⁻⁶ per AFLP fragment (locus) per generation, whereas the effective rate by which a mutation from avirulence to virulence was established in the pathogen population, when subject to selection by host resistance genes, was approximately three orders of magnitude faster.